Reconfiguring process in public administration a review and description of innovative approaches in microfinance - Antonio, Michael G. (Philippine Journal of Public Administration, 2014)
The article describes the evolution of microfinance in terms of its product lin, methodology, outreach and means of ensuring both sustainability and viability. The study outlines the innovations undertaken by microfinance institutions (MFIs) in terms of strengthening their respective institutional capability of providing better microfinance services to meet the changing demands of the market. It also provides an account of best practices formulated and adopted by microfinance institutions. Employing a desk review method, the study examined related literature on MFIS that dealt with the innovations of microfinance products and services with regard to enhancing MFIs sustainability and their responsiveness to their intended clientele. Key issues pertinent to the innovations identified were access to funding, establishing partnership between microfinance institutions and public and private enterprises, use of technology to increase access to microfinance products and services, introduction of new microfinance products, and utilizing non-conventional delivery systems to expand outreach.